The ownership of English in Taiwan. Issue 3 (6th July 2015) - SEILHAMER, MARK F.
ABSTRACT Although applied linguists have long asserted that individuals who have learned English as an additional language can rightly claim ownership of the language, this willingness on the part of academics to grant ownership to all users of English is ultimately of little consequence to the users themselves, who more often than not consider linguistic ownership to be determined solely by ethnicity or place of birth. This paper outlines a framework comprised of three aspects of language ownership—prevalent usage, affective belonging, and legitimate knowledge—and subsequently applies these concepts to a multi‐case ethnographic study of English ownership (and lack thereof) among a group of Taiwanese English learners/users who privileged different ownership dimensions. Prevalent usage was found to be very important for achieving any degree of ownership, and the ability to make overt ownership claims ultimately depended on confidence and agency.